Multi frame synchrotron radiography of pulsed power driven underwater single wire explosions - Yanuka,D; Rososhek,A; Theocharous,S; Bland,SN; Krasik,YE; Olbinado,MP; Rack,A (Journal of Applied Physics, 2018)
We present the first use of synchrotron-based phase contrast radiography to study pulsed-power driven high energy density physics experiments. Underwater electrical wire explosions have become of interest to the wider physics community due to their ability to study material properties at extreme conditions and efficiently couple stored electrical energy into intense shock waves in water. The latter can be shaped to provide convergent implosions, resulting in very high pressures (1-10 Mbar) produced on relatively small pulsed power facilities (100s of kA-MA). Multiple experiments have explored single-wire explosions in water, hoping to understand the underlying physics and better optimize this energy transfer process; however, diagnostics can be limited. Optical imaging diagnostics are usually obscured by the shock wave itself; and until now, diode-based X-ray radiography has been of relatively low resolution and rather a broad x-ray energy spectrum. Utilising phase contrast imaging capabilities of the ID19 beamline at the European Synchrotron Radiation Facility, we were able to image both the exploding wire and the shock wave. Probing radiation of 20-50 keV radiographed 200 μm tungsten and copper wires, in ∼2-cm diameter water cylinders with resolutions of 8 μm and 32 μm. The wires were exploded by a ∼30-kA, 500-ns compact pulser, and 128 radiographs, each with a 100-ps X-ray pulse exposure, spaced at 704 ns apart were taken in each experiment. Abel inversion was used to obtain the density profile of the wires, and the results are compared to two dimensional hydrodynamic and one dimensional magnetohydrodynamic simulations.